A Study of the Accounting System and Standards in Bulgaria - Stefania Vignini (Australasian Accounting, Business and Finance Journal, 2022)
This paper is focused on the analysis of Bulgarian accounting system and practices. More specifically, it is aimed at investigating the main environmental factors, which led to the development of such system. The approach is therefore both descriptive and causal. The findings suggest that the changes in the socio-economic and the cultural tradition mainly affect accounting systems and practices, as well as the status of the accounting profession.
Keywords: professional auditor judgment; risk; internal audit; Bulgaria